Colour changes, nitrite content and rehydration capacity of edible bird's nest by advanced drying method - Gan, Shu Hui; Ong, Sze Pheng; Chin, Nyuk Ling; Law, Chung Lim (Taylor & Francis, 2016)
This article presents the authors’ first attempt to improve quality of edible bird’s nest through continuous and intermittent low-temperature drying (25 and 40°C) with infrared and ultraviolet C (UVC) treatments. The attributes of quality were compared in regard to quality of hot-air-dried samples at 70–90°C. Experimental results showed that a significant improvement in the quality of edible bird’s nest in terms of minimizing color changes and rehydration capacity using intermittent low-temperature drying with infrared and UVC drying profile. However, it was also found that any drying method has less significant effect on the nitrite content of edible bird’s nest.